Creativity Sweepstakes New York City Ballet's Diamond Project assessed - Barnes, Clive 1927-2008 (Dance Books Ltd., Alton,Hampshire (UK), 2002)
New York City Ballet's Diamond Project. Wheeldon's latest adventure into movement has started - the audience can sit back and be quietly amazed. PALABRAS CLAVE: New York City Ballet, Diamond Project, Peter Martins, George Balanchine, Jerome Robbins, Frederick Wheeldon.